Scoop of joy la crèmè glacèè - Ruzmi, Nadirah; Ahmad Adzha, Nabila Irany; Ahmad Fadzli Sham, Misya Izzati; Sulaiman, Maimunah; Zamri, Maryam Nadzirah (2021)
Scope of Joy Enterprise is new company located at PT 10234, Taman Sri Medang 3, Kampung Tembila, 22200, Besut, Terengganu. Besut is a district in Terengganu and bordered by the state of Kelantan and very well knows as an attractive place especially in tourism cause of Perhentian Island one of the popular islands in Malaysia. Besides, there are many of institute of education which are developed by both the central and Terengganu state governments such as Universiti Sultan Zainal Abidin, Institute of Teacher's Education Sultan Mizan Campus, MARA Junior Science College (Kota Putra & Besut), Kolej Komuniti Besut etc. We believe this place most suitable to run our business because the growth and developing economic to targeting the customers comes with bonus the top local place to visit when come to Besut. The company of Scope of Joy Enterprise offers premium flavour ice-cream products and service for customer at same time providing the variety of flavour to give satisfactions of consumer. Our client from middle class and upper class can afford this product because of affordable prices. In addition, we also targeting the customers in the office or quarantine or most of them busiest to find something tasty, sweet and cold by doing delivery service at the door step into the customer house. This company promise the customer the premium ice-flavour complete with side dish suitable for any occasions or event.